Gaya Belajar Mahasiswa Reguler Angkatan 2005 Program Sarjana Keperawatan Universitas Jenderal Soedirman Purwokerto - Purwandari, Haryatiningsih; Saryono, (Jurnal Keperawatan Soedirman, 2007)
Understanding toward learning process and students’learning-achievement need knowledge about how someone learns. Learning style early detection helps students to understand their owned learning modalities. Learning style is a combination of how individual perceive, manage and process information. The goal of this research was to understand learning style description (learning modalities and brain’s domination) which dominantly existed in students of regular undergraduate nursing program 2005 enrollment. Survey method was used in this research which included 51 participants from regular undergraduate nursing program 2005 enrollment as sample. Purposive sampling was used. This research conducted in May to June 2006. Result showed that learning modalities in students of regular undergraduate program 2005 enrolment were visual (43,1 %), auditory (29,4%), kinesthetic (15,7 %), visual-auditory (2%), visual-kinesthetic (3,9%), auditory-kinesthetic (3,9%), and visual-auditory-kinesthetic (2%). Besides, brain domination pattern they owned were abstract non-linear/AA (43,1 %), sequential-concrete/SK (29,4%), sequential-abstract/SA (9,8%), combination SK-SA /sequential (5,9%), concrete non-linear (3,9%) balance all (3,9%) non linear/combination AA-AK (2%), and concrete/combination SK-AA (22%) The learning style involved learning modalities and brain’s domination . The students of regular undergraduate nursing program 2005 enrollment, had the learning modalities that was dominated with visual (43,1%). They also had abstract- non linear of brain’s domination, equal to 43,1%.